Spanish Regional Heterogeneity on Communting by Car to Work: Differences of Behaviour or Composition? - Módenes-Cabrerizo, Juan Antonio; Menacho-Montes, Teresa (Revista de Estudios Andaluces, 2019)
Environmental and social sustainability of commuting to work is an increasingly relevant line of research. The starting point of this paper is that a significant internal territorial heterogeneity persists on aggregate indexes of car use and that it is important to measure and understand this process correctly. This contribution propose the method of decomposition of aggregate rates (Das Gupta) as a valid methodology to understand correctly regional heterogeneity. Part of these geographical differences (between regions, degree of urbanization) is explained by a real behaviour gap. However, the sociodemographic and territorial compositions of the working populations are important as well. That is because the propensity to use the private vehicle varies along certain characteristics of the workers, and regional population structures linked to those characteristics are heterogeneous. From a policy point of view, to control (and eventually reduce) the use of cars in labour daily mobility must take into account both behaviour and composition factors. Corrective measures that only point to the behaviour of people might fail if they do not take into account the momentum of sociodemographic structures.